The Importance of Education in Peace Marketing - Margarita Išoraitė (Integrated Journal of Business and Economics (IJBE), 2019)
Peace defined means the absence of war. War and peace have always been not only military but also political issues advantage. Educational systems are confronted with exceptional challenges during violent conflict. During the conflict International humanitarian law is particularly important. Geneva Conventions a specific reference to protection related to education in wartime. Education peace is also related to the creation of values and skills that help students achieve fullness a life that embraces all people. Education peace relates to aid pupils to recognize many forms and causes violence and promote values and skills to live society. Peace marketing is trying to influence social behavior, change attitudes, habits, and not to the marketing person, but to  the benefits of society in general. Article analyzes peace education concepts, role education in promoting peace marketing, universities peace initiative.